Investigation of the passivation-induced VTH shift in p-GaN HEMTs with Au-free gate-first process. (July 2021) - Tang, Shun-Wei; Huang, Zhen-Hong; Chen, Yi-Cheng; Wu, Cheng-Hung; Lin, Pin-Hau; Chen, Zheng-Chen; Lu, Ming-Hao; Kao, Kuo-Hsing; Wu, Tian-Li
Abstract: In this work, we observe the distinct VTH characteristics in the Au-free gate-first processing p-GaN/AlGaN/GaN HEMTs with two commonly used passivation layers, i.e., SiN and SiO2 . The lower incorporated H was found in the p-GaN/AlGaN/GaN heterostructure with higher activation anneal temperature (i.e., 700 °C). Furthermore, Photoluminescence (PL) spectrum demonstrates a higher blue luminescence (BL) intensity after higher annealing treatment. The X-ray photoelectron spectroscopy (XPS) spectrum near valence band edge depicts a similar valence band maximum (VBM) characteristic, by means no impact on p-GaN surface bending by using distinct thermal treatment. The device with SiN shows a depletion-mode (D-mode) characteristic (VTH  ~ -5 V) whereas the device with SiO2 passivation exhibits an enhancement-mode ( E -mode) characteristic (VTH  ~ +0.7 V). Moreover, Transmission Line Model (TLM) devices are fabricated to investigate the effects of the passivation on two-dimensional electron gas (2DEG) in p-GaN/AlGaN/GaN stack. The results indicate that a low Rsh is obtained while passivating device surface with SiN layer, suggesting that 2DEG is present, which is most probably due to an unfunctional p-GaN layer. The secondary ion mass spectrometry (SIMS) results indicate a high hydrogen intensity in the p-GaN/AlGaN/GaN stack with a SiN passivation layer. Thus, the p-GaN deactivation process that correlates to the formation of complex MgH after SiN passivation is proposed to explain the D-mode characteristic in the device with a SiN passivation layer.